2386. Efficacy of Lefamulin (LEF) vs. Moxifloxacin (MOX) Against Common Pathogens in Adults With Community-Acquired Bacterial Pneumonia (CABP): Results From the Phase 3 Lefamulin Evaluation Against Pneumonia (LEAP 1) Study. (26th November 2018) - File, Thomas; Goldberg, Lisa; Paukner, Susanne; Das, Anita; Gelone, Steven P; Saviski, John; Sweeney, Carolyn; Seltzer, Elyse; Talbot, George H; Gasink, Leanne B
Abstract: Background: New CABP treatments with targeted activity and improved tolerability are needed. LEF, a novel pleuromutilin antibiotic that binds to a conserved region of the bacterial ribosome, is in development for IV or oral CABP treatment. This Phase 3 clinical study evaluated the efficacy of LEF vs. MOX in adults with CABP. Methods: In this multicenter, randomized, double-blind study, 551 adult patients with CABP (Patient Outcomes Research Team Risk Class ≥III) were randomized to LEF 150 mg IV Q12 hours ( n = 276) or MOX 400 mg IV Q24 hours ( n = 275). After 6 IV doses, qualifying patients could be switched to oral therapy. Adjunctive linezolid was given with MOX for suspected methicillin-resistant S. aureus . Primary outcomes were early clinical response (ECR) in the intent-to-treat (ITT) population (FDA endpoint), and investigator assessment of clinical response (IACR) at test of cure in the modified ITT (mITT) and clinically evaluable (CE-TOC) populations (co-primary EMA endpoints). The microITT population included all patients with a baseline CABP pathogen detected by respiratory tract or blood culture, urinary antigen test, serology, and real-time PCR from sputum, oropharyngeal and nasopharyngeal swabs. The microITT2 population included patients with a CABP pathogen detected by methods excluding PCR. Confirmatory identification and susceptibility testing of isolates, serology, and PCR were performed by a central laboratory. Results: LEF was noninferior to MOX for ECR and IACR (LEF 87.3% [ITT], 81.7% [mITT], 86.9% [CE-TOC]; MOX 90.2% [ITT], 84.2% [mITT], 89.4% [CE-TOC]). The most common pathogen identified was S. pneumoniae . In the microITT population ( n = 159 per arm), LEF and MOX demonstrated similar ECR and IACR rates (figure). LEF was efficacious against S. pneumoniae (including resistant phenotypes), H. influenzae, M. catarrhalis, S. aureus, and atypical pathogens. In the microITT2 population, response rates remained similar across baseline pathogens but showed more variation likely due to smaller sample sizes. Conclusion: In this first Phase 3 clinical trial, LEF showed similar efficacy to MOX against the most commonly identified CABP pathogens. LEF demonstrates promise as a targeted monotherapy for the treatment of CABP in adults. Disclosures: T. File, BioMerieux: Scientific Advisor, Consulting fee. Curetis: Scientific Advisor, Consulting fee. Melinta: Scientific Advisor, Consulting fee. Merck: Scientific Advisor, Consulting fee. MotifBio: Scientific Advisor, Consulting fee. Nabriva: Investigator and Scientific Advisor, Consulting fee and Research grant. Pfizer: Scientific Advisor, Consulting fee. Paratek: Scientific Advisor, Consulting fee. L. Goldberg, Nabriva: Employee, Employee Stock Options and Salary. S. Paukner, Nabriva: Employee and Shareholder, Salary. A. Das, Achaogen: Consultant, Consulting fee. Cempra: Consultant, Consulting fee. Contrafect: Consultant, Consulting fee. Paratek: Consultant, Consulting fee. Tetraphase: Consultant, Consulting fee. Wockhardt: Consultant, Consulting fee. Theravance: Consultant, Consulting fee. Zavante: Consultant, Consulting fee. UTILITY: Consultant, Consulting fee. S. P. Gelone, Nabriva Therapeutics: Employee, Equity, Shareholder and Salary. Achaogen: Shareholder, Equity, Shareholder. J. Saviski, Nabrica Therapeutics, plc: Employee, Salary. C. Sweeney, Nabriva: Employee, employee stock options and Salary. E. Seltzer, Nabriva (previous employee and salary): Employee and Shareholder, Salary. G. H. Talbot, Nabriva Therapeutics: Board Member, Consultant and Shareholder, Consulting fee and stock options, board fees. L. B. Gasink, Nabriva: Employee, Salary.